Changes in heavy metal mobility and availability from contaminated wetland soil remediated with combined biochar-compost. (August 2017) - Liang, Jie; Yang, Zhaoxue; Tang, Lin; Zeng, Guangming; Yu, Man; Li, Xiaodong; Wu, Haipeng; Qian, Yingying; Li, Xuemei; Luo, Yuan
Abstract: The combination of biochar and compost has been proven to be effective in heavy metals contaminated wetland soil restoration. However, the influence of different proportions between biochar and compost on immobilization of heavy metals in soil has been less studied up to date. Therefore, we investigated the effect of different ratios of biochar-compost mixtures on availability and speciation distribution of heavy metals (Cd, Zn and Cu) in wetland soil. The results showed that applying all amendment combinations into wetland soil increased gradually the total organic carbon (TOC) and water-extract organic carbon (WEOC) as the compost percentage rose in biochar-composts. The higher pH was obtained in a certain biochar addition (20% and 40%) in combinations due to efficient interaction of biochar with compost. All amendments could significantly decrease availability of Cd and Zn mainly from pH change, but increase available Cu concentration as the result of increased water-extract organic carbon and high total Cu content in compost. Moreover, amendments can decrease easily exchangeable fraction and increase reducible of Cd and Zn greatly with increase of compost content in combinations, while amendments containing compost promote transformation of Cu from Fe/Mn oxide and residual fractions to organic bindings. These results demonstrate that different ratios of biochar and compost have a significant effect on availability and speciation of heavy metals in multi-metal-contaminated wetland soil. Graphical abstract: Highlights: 20% and 40% biochar addition in amendment combinations result in the higher soil pH. The pH changes explained the availability changes of Cd and Zn. Cu availability was related to high WEOC and total Cu content in compost. The increased organic binding fraction of Cu derived from the transformation of Fe/Mn oxide and residual fractions.